Numerical Calculation of Stress Intensity Factor of Tooth Root Crack in the High-speed EMU Gear - Li Xiuhong; Wang Yubin; Li Wenhui; Qin Xiaofeng; Pang Yinming (Jixie chuandong)
In order to research the stress intensity factor of tooth root of the high-speed EMU gear,the location of crack initiation is determined by combining the finite element method and mapping method. The stress intensity factor of the different nodes of the initial crack tip of the tooth root is calculated by Abaqus based on the theory of linear elastic fracture mechanics,then by contrast,the type I stress intensity factor is dominant in the crack propagation. Based on the obtained result,the influence of load magnitude,crack radius and crack shape on the mode I stress intensity factor is discussed. The results indicate that the influence of load magnitude on the modeⅠstress intensity factor is obvious and linear. The influence of crack shape on the distribution of mode I stress intensity factor in the crack front is very obvious.